2020
DOI: 10.1039/d0ra01549k
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol synthesis of TiO2:Er3+/Yb3+ submicron-sized spherical particles and upconversion optimization for application as anti-counterfeiting materials

Abstract: TiO2:Er/Yb spherical particles were synthesized by spray pyrolysis and their luminescence was optimized for application as anti-counterfeiting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Jung 26 reported that the main UC emission color of TiO 2 :Er 3+ /Yb 3+ phosphors is rather controlled by the Yb 3+ than the concentration of Er 3+ – with increasing Yb 3+ ions concentration the red-to-green ratio increased significantly. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung 26 reported that the main UC emission color of TiO 2 :Er 3+ /Yb 3+ phosphors is rather controlled by the Yb 3+ than the concentration of Er 3+ – with increasing Yb 3+ ions concentration the red-to-green ratio increased significantly. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Johannsen et al 25 showed that changes in host crystallinity in Er 3+ doped TiO 2 films deposited on Si (100) substrates significantly modified its luminescence properties. Moreover, red-to-green emission ratio relate to Er 3+ /Yb 3+ concentration ratio as presented by Jung, 26 while blue or UV light emission is observed only for UC materials with high efficiency due to low probability of the three or four photon UC processes. 9 …”
Section: Introductionmentioning
confidence: 84%
“…This issue has a signicantly negative impact on the global economy, human health, and scientic advancement. [487][488][489] Therefore, it is imperative to create advanced anti-counterfeiting technology to deal with the effects of counterfeiting on diverse elds and protect the welfare of consumers. Numerous anti-counterfeiting techniques, such as barcoding, watermarking, the digital signature standard (DSS), radio frequency identication tags (RFIDs), holograms, and uorescent tags or levels, have been employed so far.…”
Section: In Vivo and Vitro Sensingmentioning
confidence: 99%
“…This is due to the mismatch of the ionic radius and the preparation method. Most works to date have been prepared using sol-gel, co-precipitation, solid sintering, or physical mixing. For example, in the commonly used sol-gel method, Er 3+ and Yb 3+ first form a mixed colloid with titanium precursor in the aqueous phase and then prepare into nanoparticles through hydrothermal or solvothermal processes. However, this method often results in self-aggregation of dopants and titanium precursors, making it difficult for the doped ions to be embedded into the TiO 2 lattice and forming rare earth oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%